English Language Education in Nepal: Need or Hegemony? - Khanal, Govinda Prasad (Marsyangdi Journal, 2022)
English language teaching (ELT) has become much pervasive in Nepal in the recent decades since its entry in the mid nineteenth century. Recently, the trend of converting government aided community schools into English medium has become a common phenomenon throughout Nepal. This paper intends to explore the hegemonial nature of English language education in Nepal, which has pressurised several local languages including Nepali, the official language of Nepal. I have reviewed some documents to establish how expansion of English has pressurised the growth of indigenous languages including Nepali, with the possibility of the loss of indigenous properties including languages, cultures and values. It pictures out the possibility of hybridity in language and culture in the new generations of youths and children if undue priority to ELT continues in the academia.